EIF Business Angels Survey 2021/22: Market sentiment - Antonia Botsari; Stella Kupres; Frank Lang; Davide Legnani; Filip Mandys (European Investment Fund (EIF), 2022)
The EIF Business Angels Survey, together with the EIF VC Survey and the EIF Private Equity Mid-Market Survey (the largest combined regular survey exercises among GPs and Business Angels on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2021/22 EIF Business Angels Survey. The paper focuses on the market sentiment and the impact of COVID-19. The study looks at the market situation, developments in the recent past and expectations for the future. The main results are summarised and compared over time. The publication provides a valuable insight of the developments and the markets in 2021/22, as well as an outlook for the near future. The EIF Working Papers are designed to make available to a wider readership selected topics and studies in relation to EIF's business. The Working Papers are edited by EIF's Research & Market Analysis and are typically authored or co-authored by EIF staff or are written in cooperation with EIF.
Keywords: 330; Business Angels; Branchenentwicklung; Befragung; EU-Staaten